LIGHT POLLUTION IN LEO-SATELLITE TRACKING - Shakun, L. S.; Marsakova, V. I.; Golubovskaya, T. A.; Terpan, S. S.; Melikyants, S. M.; Korobeynikova, E. A. (Одеські астрономічні публікації, 2016)
Because of the high level of the light pollution in Odessa city, only the observations of LEO (low Earth orbit)-satellites are performed in the main office of the Astronomical observatory of Odessa National University named after I.I. Mechnikov. As the one of the observation results we obtain the sky background measurements along the satellite’s way through the sky (at different azimuths and altitudes that change during the satellite tracking). We propose the method of irregular extinction changes diagnostics that realized by using the different data filtration methods. Also as the result of our analysis of these observations we present azimuth-altitude diagram of sky background that shows the most significant light pollution at the north-western and northern directions caused by the Port of Odessa and the stadium “Chernomorets”.